The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1523/jneurosci.3515-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Tyrosine Phosphatase Shp2 Is Required for the Generation of Oligodendrocyte Progenitor Cells and Myelination in the Mouse Telencephalon

Abstract: The protein tyrosine phosphatase Shp2 (PTPN11) is crucial for normal brain development and has been implicated in dorsal telencephalic neuronal and astroglia cell fate decisions. However, its roles in the ventral telencephalon and during oligodendrogenesis in the telencephalon remain largely unknown. Shp2 gain-of-function (GOF) mutations are observed in Noonan syndrome, a type of RASopathy associated with multiple phenotypes, including cardiovascular, craniofacial, and neurocognitive abnormalities. To gain ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…In western blot, it recognizes a single 170 kDa band on NIH/3T3 whole cell lysates (manufacturer's datasheet). This antibody has previously been used to identify OPCs in the mouse telencephalon (see e.g., Ehrman et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In western blot, it recognizes a single 170 kDa band on NIH/3T3 whole cell lysates (manufacturer's datasheet). This antibody has previously been used to identify OPCs in the mouse telencephalon (see e.g., Ehrman et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…This antibody has previously been used to identify OPCs in the mouse telencephalon (see e.g., Ehrman et al, 2014).…”
Section: Tissue Preparationmentioning
confidence: 99%
“…Of note, conditional ablation of Braf in mouse neuroglial precursor cells was shown to result in defective myelination and oligodendrocyte differentiation [Galabova‐Kovacs et al., ]. Similarly, loss of Shp2 in the oligodendrocyte lineage, as well as transgenic expression of a NS‐associated Shp2 gain‐of‐function allele, results in severe abnormal myelination phenotypes [Ehrman et al., ]. Hence, the myelination defect observed in some individuals with a CBL mutation adds support to the impact of dysregulated RAS signaling on glial cell development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gauthier and colleagues showed that knocking down SHP2 blocked neurogenesis and enhanced astrogenesis, suggesting that SHP2 plays a pivotal role in determining neuronal cell fate (Gauthier et al, 2007). A recent study showed that SHP2 also regulates the generation of oligodendrocyte progenitor cells in the mouse ventral telencephalon (Ehrman, Nardini, Ehrman, Rizvi, Gulick, Krenz et al, 2014). Importantly, gain-of-function mutations of PTPN11 are highly associated with the NS, which is a common autosomal dominant genetic disorder characterized by congenital heart defects, facial abnormalities, delayed growth, and cognitive impairment (Romano, Allanson, Dahlgren, Gelb, Hall, Pierpont et al, 2010).…”
Section: Shp2 and Nsmentioning
confidence: 99%